Knowledge and Practices of Healthcare Providers towards Infection Prevention and Its Associated Factors in Saudi Arabia - Abdulaziz Abdullah Abdulaziz Alhassan, Abdulrahman Ibrhim Abdulaziz Alshnaber, Turki Marzouq Alotaibi, Fahad Halel Alomairy, Mohammed Khalaf Ghazj Alhalaj, Khalid Abdullah Salem Alsalem, Noor Mohammad Almotairi, Mohammed Ali Mofareh Alsumaydi; Fawaz Saad Saif Alrwais, Sami Saad Alrabiah, Sulaiman Saad Sulaiman Alrabiah, Saeed Mesfer Alahmadi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Adherence to infection prevention and control practices is essential to providing safe and high quality patient care across all settings where healthcare is delivered.Hospital-acquired infections (HAIs) contribute to increased length of hospital stay, higher mortality and higher health-care costs. Prevention and control of HAIs is a critical public health concern.Adequate knowledge and safe practice of infection prevention among healthcare providers are vital to prevent nosocomial infections. This study aimed: To assess the level of knowledge and practices of healthcare providers (HCPs) towards infection prevention and its associated factors in hospitals at Jeddah, Saudi Arabia. Materials and Methods: A cross-sectional study was conducted among 171 HCPs who were selected by a convenient technique. Data were collected using interviewer-administered questionnaire.Multivariable logistic regression was performed to identify factors associated with knowledge and practice of infection prevention. Result: The percentage of HCPs with sufficient knowledge and safe infection prevention practices was around 70.8% and 55.0%, respectively. Adequate knowledge of infection prevention was positively correlated with having five years or more of work experience (AOR = 1.52: 95%CI; 1.13, 4.51), working in a maternity unit (AOR = 1.67:95%CI; 1.38–5.23), taking infection prevention training (AOR = 2.2, 95% CI; 1.01, 4.75), and having infection prevention guidelines (AOR = 3.65, 95% CI; 1.26, 10.54). The odds of safe practice were lower for HCPs working in a facility without a continuous water supply (AOR = 0.48:95% CI; 0.21, 0.83), but greater for those who received infection prevention training (AOR: 2.4; 95% CI; 1.01, 4.75). Conclusion: A considerable percentage of health care professionals lacked sufficient knowledge and engaged in risky infection prevention practices. In order to enhance healthcare workers’ understanding of infection prevention, sufficient pre-service and on-the-job training should be provided.